2018
DOI: 10.1007/5584_2018_193
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient-Specific Instrumentation Improve Femoral and Tibial Component Alignment in Total Knee Arthroplasty? A Prospective Randomized Study

Abstract: Alignment of the prosthesis is one of the most significant factors that affect the long-term clinical outcome following total knee arthroplasty (TKA). There is conflicting evidence whether patient-specific instrumentation (PSI) for TKA improves the component position compared to standard instrumentation. This study aimed to compare the rotational alignment of the femoral and tibial components in TKA patients when performed with either conventional or PSI. Sixty patients with primary knee osteoarthritis were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The Knee Society Score was reported in 16 studies [ 19 29 , 31 , 34 , 35 , 37 , 38 ]. KSS Functional score was significantly higher in the PSI group (favouring PSI) at 24 months in the 5 studies compared (mean difference 4.36, 95% confidence interval 1.83–6.89), with moderate heterogeneity (I 2 = 66%) [ 19 , 20 , 22 , 26 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Knee Society Score was reported in 16 studies [ 19 29 , 31 , 34 , 35 , 37 , 38 ]. KSS Functional score was significantly higher in the PSI group (favouring PSI) at 24 months in the 5 studies compared (mean difference 4.36, 95% confidence interval 1.83–6.89), with moderate heterogeneity (I 2 = 66%) [ 19 , 20 , 22 , 26 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, PSI systems have not demonstrated improved accuracy when compared with manual instrumentation techniques in several published studies. [19][20][21][22][23][24] In another PSI-TKA study, the investigators reported a requirement for intraoperative modifications in the majority of cases with the use of a noncustomized implant design. 25 While manually instrumented TKA may accommodate intraoperative modification, it is not clear whether this would be either feasible or appropriate for a CIM-TKA placed using PSI technology.…”
mentioning
confidence: 99%
“…In other studies, we have found that whether the patella is resurfaced in TKA has no significant differences in the KSS or the WOMAC score [2,30,31]. Other studies that examined the effects of using different surgical techniques as well as their use of various instruments and prostheses also reported that these factors had no relationship with these scores [32][33][34]. Therefore, we believe that better knee function may be more relevant to basic principles including excellent lower limb alignment, proper prothesis position, integrated ligaments, and greater lower limb strength.…”
Section: Discussionmentioning
confidence: 91%